(3eMGhQ GdJehjd GdGSJQGJjLjs - (3aQjO(B, (3GdfLGQs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2009)
(3ebOeI aj CShGb GdeGd h GdeDSSGJ GdeGdjI , YdGbI GdeOjQ GdeGdj HGdHfhc GdJLGQjI , GdLhGfH GdELQGFjI h GdJfXjejI ddHfhc , EOGQI GHfhc HGdLhOI GdTGedI , GdeOjQ GdeGdj h GdeDSSGJ GdeGdjI ZjQ GdeUQajI , GdeOjQ GdeGdj h GdGShGb GdeGdjI , GdeOjQ GdeGdj h CShGb QCS GdeGd aj GdOhd GdYQHjI , ejJbHd hXGFa GdGOGQI GdeGdjI GdGSJQGJjLjIs
(3eQGLY U(B.259 (3, LOGhd U(B.261s
Keywords: (3CShGb GdeGds; (3GdJehjds; (3GdeDSSGJ GdeGdjIs